A new design of composites for thermal management: Aluminium reinforced with continuous CVD diamond coated W spiral wires. (5th July 2016) - Ma, Li; Zhang, Long; Zhao, Pengyu; Hu, Naixiu; Gong, Zhenzhi; Ye, Wentao; Wei, Quiping; Zhou, Kechao; Yu, Zhiming; Zhang, Yuefeng
Abstract: A novel design of Al matrix composite reinforced with diamond coated spiral tungsten wire is proposed for thermal management. Fabrication techniques of the diamond film reinforced Al matrix composites consist of hot filament assisted chemical vapour deposition (HFCVD) for diamond film, low-cost cold pressing and vacuum sintering of Al matrix composites. The microstructure characteristics and thermal properties of the composites have been studied. Results show that the diamond film retains its high quality and integrity after the vacuum sintering process. Even such a low content of diamond films in the filler- at most 6.5 vol.% - provides a thermal conductivity of 294 W/mK, about 69% higher than that of sintered Al and 79% higher than that of 6.5 vol.% diamond particles reinforced Al matrix composite fabricated by the same powder metallurgy process. Finite element analysis of heat transfer within such a structure is conducted, revealing that the continuous and thick diamond framework provides continuous channels and effective thermal conductive pathways for heat transfer. This work displays a great potential of CVD diamond films reinforced metal matrix composites for thermal conduction applications. Graphical abstract: A novel CVD diamond spiral wire/aluminium composite was designed and fabricated. A continuous diamond channel for heat transfer was designed and fabricated. Good adhesion between uncoated diamond film and pure Al was produced. The TC of the composite was enhanced by 79% compared with diamond particles/Al composites. Highlights: A novel CVD diamond coated W spiral wires/aluminium composite was designed and fabricated. A continuous diamond channel for heat transfer was designed and fabricated. Good adhesion between uncoated diamond film and pure Al was produced. The TC of the composite was enhanced by 79% compared with diamond particles/Al composites.